Diagnostic Value of Methylated Septin9 for Colorectal Cancer Detection - Xie, Li; Jiang, Xiyi; Li, Qian; Sun, Zujun; Quan, Wenqiang; Duan, Yuping; Li, Dong; Chen, Tianhui (Frontiers in Oncology, 2018)
Background Methylated Septin9 (mSEPT9) has been suggested as a reliable biomarker in colorectal cancer (CRC) detection. We aimed to determine the diagnostic value of mSEPT9 for CRC detection in Chinese patients. In addition, we compared the diagnostic efficacy of mSEPT9 to traditional screening method [fecal occult blood test (FOBT)] and two biomarkers [carcinoembryonic antigen (CEA) and carbohydrate antigen-199 (Ca-199)]. Methods Overall 248 subjects including 123 patients with CRC and 125 controls were included. Plasma and fecal samples were collected for CEA, Ca-199, mSEPT9, and FOBT tests. Sensitivity and specificity were calculated to evaluate the diagnostic efficacy of each method; receiver operating characteristic (ROC) curve was plotted for the assessment of diagnostic accuracy, and comparisons among FOBT, mSEPT9, and the combination were assessed through area under the ROC curve (AUC). Results mSEPT9 achieved overall sensitivity and specificity of 61.8% [95% confidence interval (CI): 53.0–69.9%] and 89.6% (83.0–93.8%), respectively, with an AUC value of 0.757 (95% CI: 0.701–0.807), superior to FOBT [sensitivity: 61.4% (50.9–70.9%); specificity: 70.3% (59.1–79.5%); AUC: 0.658 (0.578–0.723)], CEA [sensitivity: 35.0% (27.1–43.7%); specificity: 62.6% (53.8–70.7%); AUC: 0.485 (0.411–0.559)], and Ca-199 [sensitivity: 17.9% (12.1–25.6%); specificity: 55.7% (48.9–64.1%); AUC: 0.353 (0.283–0.423)]. The combination of mSEPT9 and FOBT further improved sensitivity and AUC value of 84.1% (75.1–90.3%) and 0.807 (0.752–0.863), respectively, while specificity was declined to 62.2% (50.8–72.4%). Conclusion mSEPT9 demonstrated best diagnostic ability in CRC detection compared with FOBT, CEA, and Ca-199. The combination of mSEPT9 and FOBT further improved diagnostic sensitivity especially for early stage disease, which may provide a new approach for future CRC screening, though further investigations are warranted.